Pupation depth of Microctonus spp - Ferguson, C.M.; Phillips, C.B.; Barton, D.M.; McNeill, M.R.; Townsend, H.I.; Vattala, H.D. (New Zealand Plant Protection, 2008)
Microctonus aethiopoides and M hyperodae are introduced biocontrol agents for exotic weevil pests in New Zealand Understanding how environmental factors affect their phenologies is integral to defining their impact on target and nontarget hosts To study where in the soil profile these parasitoids pupate parasitised weevils were caged either above intact soil cores containing vegetation and litter from pasture and lucerne or above crumbled bare soil After parasitoids had emerged from their hosts and pupated the substrates were searched to locate pupation sites With handsorting/ flotation 3 of 17 M hyperodae pupae were found in the top 10 mm of soil cores and 1 each at 1015 2025 3540 and 4550 mm A further 10 were at indeterminate depths within 030 mm Intact cores were searched by microscope (64X) and 28 of 32 M hyperodae and 6 of 7 M aethiopoides were found in surface litter The others were in cracks to 25 mm Initial observations with crumbled soil showed pupation had occurred but pupation depth was often undeterminable Microscopic searching revealed two M hyperodae and one M aethiopoides barely covered by soil Pupation of both parasitoid species apparently occurs at or close to the soil surface suggesting that pupal survival and development could be strongly influenced by weather